Retraction: Monotherapy with meropenem versus combination therapy of ceftazidime plus amikacin for empirical treatment of cancer patients with Febrile Neutropenic (FN): systematic review and meta-analysis - Wang, Li; Teng, Zhaowei; Cai, Defang (European Journal of Oncology and Environmental Health, 2016)
Article retracted after publication